Content and Frequency of Writing on Diabetes Bulletin Boards: Does Race Make a Difference? - Case, Siobhan; Jernigan, Valarie; Gardner, Audra; Ritter, Philip; Heaney, Catherine A; Lorig, Kate R (JMIR Publications, 2009)
Background Diabetes-related disparities are well documented among racial minority groups in the United States. Online programs hold great potential for reducing these disparities. However, little is known about how people of different races utilize and communicate in such groups. This type of research is necessary to ensure that online programs respond to the needs of diverse populations. Objective This exploratory study investigated message frequency and content on bulletin boards by race in the Internet Diabetes Self-Management Program (IDSMP). Two questions were asked: (1) Do participants of different races utilize bulletin boards with different frequency? (2) Do message, content, and communication style differ by race? If so, how? Methods Subjects were drawn by purposeful sampling from participants in an ongoing study of the effectiveness of the IDSMP. All subjects had completed a 6-week intervention that included the opportunity to use four diabetes-specific bulletin boards. The sample (N = 45) consisted of three groups of 15 participants, each who self-identified as American Indian or Alaskan Native (AI/AN), African American (AA), or Caucasian, and was stratified by gender, age, and education. Utilization was assessed by counting the number of messages per participant and the range of days of participation. Messages were coded blindly for message type, content, and communication style. Data were analyzed using descriptive and nonparametric statistics. Results In assessing board utilization, AAs wrote fewer overall messages (P = .02) and AIs/ANs wrote fewer action planning posts (P = .05) compared with Caucasians. AIs/ANs logged in to the program for a shorter time period than Caucasians (P = .04). For message content, there were no statistical (P ≤ .05) differences among groups in message type. No differences were found in message content between AAs and Caucasians, but AIs/ANs differed in content from both other groups. Caucasians wrote more on food behaviors than AIs/ANs (P = .01), and AIs/ANs wrote more about physical activity than Caucasians (P = .05) and about walking than the other two groups (P = .01). There were no differences in communication style. Conclusions Although Caucasians utilized the boards more than the other two groups, there were few differences in message type, content, or style. Since participation in bulletin boards is largely blind to race, age, gender, and other characteristics, it is not clear if finding few differences was due to this optional anonymity or because non-Caucasian participants assumed that they were communicating with Caucasians. If the low variability between racial groups indicates that the IDSMP is flexible enough to meet the needs of multiple racial groups, then online programs may be an accessible and effective tool to reduce health disparities. These questions need to be investigated in future studies. Trial Registration Parent trials: Clinicaltrials.gov NCT00372463 and NCT00185601; http://clinicaltrials.gov/ct2/show/NCT00372463 and http://clinicaltrials.gov/ct2/show/NCT00185601 (archived by WebCite at http://www.webcitation.org/5hm2g0AeX and http://www.webcitation.org/5hm2i4XVw)